Demographic and Media Factors Affecting Women’s Demand for Different types of Health Insurance: Evidence from a Developing Country - Musoke, Edward; Ssekiziyivu, Bob; Mukoki, James; Ashaba, Claire (F1000Research, 2022)
In the absence of a National Health Insurance Scheme, many Ugandans don’t have access to basic health care because of the high cost of attaining this health care. The problem is even worse among women who are faced with higher rates of morbidity and hospitalization. The objective of the study was to assess demographic and media factors affecting the demand for community, employer provided and private health insurance among women in Uganda. The study used secondary data from the 2016 Uganda Demographic Health Survey, a nationally representative survey. The sample comprised of 18,506 women aged 15-49 years from a population of 20,880 households. Data were analyzed using STATA version 15. Descriptive statistics, Chi square tests and the Firth logistic regression were used to understand the frequency distribution of different types of health insurance, demographic and media factors, associations between different types of health insurance, demographic and media factors and the demographic and media factors affecting the demand for community, employer provided and private health insurance.The results indicated low demand for different types of health insurance among women. Education and wealth were the demographic factors that affected the demand for community and employer provided health insurance while marital status, age and education were demographic factors that affected the demand for community, employer provided and private health insurance respectively. Watching television, reading newspapers and listening to radio were the media factors that affected the demand for employer provided health insurance while listening to radio was the only media factor that affected the demand for community health insurance. There is a need to expedite the National Health Insurance policy to enhance the uptake of health insurance among women in Uganda.
Keywords: Women, health insurance, developing country